The efficacy of dexmedetomidine 100mcg as an adjuvant to 0.25% ropivacaive versus 0.5% plain ropivacaine for supraclavicular brachial plexus block in arteriovenuos fistula surgery - Mutthusamy, Prakash Seelan (2020)
Background Brachial plexus block is the preferred method of anaesthesia for Arteriovenous fistula (AVF) creation in End-Stage Renal Failure (ESRF) patients. Dexmedetomidine is an adjuvant used to improve the outcome of the block. The objective of this study was to investigate the efficacy of adding dexmedetomidine 100mcg to ropivacaine 0.25% in supraclavicular block. Methods 68 ESRF patients scheduled for AVF surgery were studied in a prospective, randomized, double-blind controlled clinical trial. They were divided into 2 groups; patients in group D receive a mixture of 30 mls of ropivacaine 0.25% and 1 ml (100 mcg) dexmedetomidine whilst patient in group C receive mixture of 30 mls of ropivacaine 0.5% and 1 ml of 0.9% normal saline. The primary endpoint was the onset and duration of sensory and motor block while secondary endpoint was to score patient and surgeon satisfaction. Results The onset time of sensory block in group D [15.29(3.24)] min was earlier than group C [18.09(3.26)] min and statistically significant (p < 0.001) while the onset time of motor block earlier in group C compare to group D but not statistically significant (p= 0.71). Both sensory and motor block durations were significantly longer in group D then group C with statistically significant (p< 0.001). In terms of satisfaction scoring group D has better scoring compare to group C among both surgeons and patients (p < 0.001). Conclusion: Low dose ropivacaine 0.25% with adjuvant of dexmedetomidine 100mcg is non inferior to the control group in providing anaesthesia for ESRF patients in AVF surgery.